Anti-fertility and abortifacient activity of hydroalcoholic fruit pulp extract of Tamarindus indica - Mandeep Kaur; Avtar Chand Rana; Sunil Kumar; Beena Kumari; Dinesh Kumar; Ashok Jangra (Elsevier, 2023)
Background: Medicinal plants have been widely used for treatment and management of various diseases. There are many different types of commercialized synthetic contraceptives on the market today for controlling fertility, these cannot be utilized since they have serious side effects such weight gain, hormonal alterations, hypertension, and cancer . In India, indigenous women from Tripura & Maharashtra have historically utilized the fruit pulp of Tamarindus Indicus to induce abortion. However, there is currently no accessible scientific data supporting the use of this plant for fertility control. Methods: The current study's objective was to evaluate the hydroalcoholic extract of Tamarindus indica fruit pulp's ability to induce abortion in female Wistar rats. In this experimental animal model, contraceptive activity of hydroalcoholic extract of Tamarindus indica (HAETI) was evaluated for anti-implantation, abortifacient, and estrogenic/antiestrogenic action. Female rats having ovariectomies were given HAETI extract (500 mg/kg) for 7 straight days to test to evaluate the estrogenic/anti-estrogenic action. All animals were killed on the eighth day, and the blood serum was then processed to determine the levels of several hormones, including LH, FSH, prolactin, estrogen, and others, as well as biochemical markers including cholesterol, total protein, glycogen, and alkaline phosphates. In this model, modifications to uterine histoarchitecture were also investigated. The extract was administered from the 1 to7 day of pregnancy. On 10th day, laparotomy was performed to evaluate the no. of implants in female rats. Results: Steroids, flavonoids, saponins, tannins, and alkaloids were detected during phytochemical analysis of the extract. the HAETI extract demonstrated significant anti-implantation and abortifacient effects. Additionally, the extract demonstrated significant estrogenic activity as evident by uterine histological parameters including increases in endometrium thickness and height, vaginal cornification. Further, the study found marked increases in glycogen, alkaline phosphate, estrogen, cholesterol levels when given alone or in combination with estradiol valerate. LH, FSH, and a little increase in prolactin levels were suppressed after HAETI administration. Conclusions: Our study's findings showed that Tamarindus indica fruit pulp hydroalcoholic extract has a potent contraceptive effect, which may be explained by the phytoconstituents of the plant's capacity to inhibit implantation and have an estrogenic effect. Further investigation on Tamarindus indica as a potential natural anti-implantation agent allow for new abortive drug.